2020
DOI: 10.3390/catal10040397
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Defects in TiO2 Semiconductor: Oxygen Vacancies in the Bulk and Surface of Rutile and Anatase

Abstract: Oxygen deficiency (O-vacancy) contributes to the photoefficiency of TiO2 semiconductors by generating electron rich active sites. In this paper, the dispersion of O-vacancies in both bulk and surface of anatase and rutile phases was computationally investigated. The results showed that the O-vacancies dispersed in single- and double-cluster forms in the anatase and rutile phases, respectively, in both bulk and surface. The distribution of the O-vacancies was (roughly) homogeneous in anatase, and heterogenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…We found that for 3.125% O vacancy concentration, = 4.1 eV, while for 12.5% O vacancy concentration, = 4.7 eV. These trends in formation energies and the relative stabilities of different O vacancy concentrations were comparable to what reported in other oxide system 33 . Note that in many semiconductors, charged O vacancy is known to be thermodynamically stable and thus energetically feasible, more so in n -type conductive systems.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We found that for 3.125% O vacancy concentration, = 4.1 eV, while for 12.5% O vacancy concentration, = 4.7 eV. These trends in formation energies and the relative stabilities of different O vacancy concentrations were comparable to what reported in other oxide system 33 . Note that in many semiconductors, charged O vacancy is known to be thermodynamically stable and thus energetically feasible, more so in n -type conductive systems.…”
Section: Resultssupporting
confidence: 87%
“…In order to understand the relative formation of different O vacancy concentrations, we calculated formation energies ( ) corresponding to two different O vacancy concentrations in our study. In this definition, , correspond to formation energy, supercell energy with single O vacancy, and the pristine supercell energy, respectively, while refers to the chemical potential of O which is half of the total energy of an isolated oxygen molecule 33 . We found that for 3.125% O vacancy concentration, = 4.1 eV, while for 12.5% O vacancy concentration, = 4.7 eV.…”
Section: Resultsmentioning
confidence: 99%
“…As the Ti-Ti distance in rutile is shorter than in anatase, the rutile TiO 2 is 9% denser. Therefore, this has caused more pronounced orbital localization of the Ti 3 d and O 2 p and resulted in a narrower bandgap [ 31 ]. In accordance with the XRD patterns in Figure 7 , the bandgap narrowing was attributed to the higher crystallinity of THNF600, in which the majority of the fraction was rutile (75.8%).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of site defects on the surface of rutile was higher than anatase because the energy needed for production of site defect on rutile was lower than anatase. [ 58 ] The BET, FESEM, and TEM data also confirmed the formation of mesopores with high surface area in MTN particles. [ 59 ] These properties have proved a great potential of MTN to be utilized as a photocatalyst.…”
Section: Resultsmentioning
confidence: 83%